Knowledge and Practice Regarding Breastfeeding among Mothers Attending Immunization Clinic in Nepalgunj Medical College Teaching Hospital - Parajuli, Janaki; Mishra, Pradip; Thapa, Narbadha (Journal of Nepalgunj Medical College, 2017)
Background: Breastfeeding has been accepted as the most vital intervention for reducing infant mortality and ensuring optimal growth and development of children. The current study aimed to assess the knowledge and practice regarding breastfeeding among mothers attending immunization clinic. Methods: A cross sectional study was mothers having children under 1 year of age, who attended their children for vaccination and for the treatment of other minor illnesses. The purposive sampling technique was used for selecting the study subjects. Information regarding patients' demographics, knowledge and practice towards breastfeeding were collected from these mothers on a pre-designed and pretested questionnaire. Results: A total of 208 women with children between 6 months and 12 months were included in the study. Their age ranged between 18 and 37 years with the mean of 24.9±4.1. Overall mother's breastfeeding knowledge was good among 35% and excellent among 22% of them while it was unsatisfactory among 43% of the mothers. Breastfeeding in the first 6 months was practiced by 42% of the participated mothers. Only 23% practiced exclusive breast feeding. Among those who breastfed their babies, 51% initiated breastfeeding in the first hour of birth, 21% between 2-4 hours and only 20% initiated it after 24 hours. Only 73% of mother had not given any prelacteal feeding to their babies. No enough breast milk (47.9%), crying hungry (31.5%), work-related problems (13.7%) & mothers' illness (6.8%) were the commonly reported barriers against exclusive breastfeeding. Conclusion: The prevalence of EBF for up to 6 months of age was still low as per WHO recommendations. The mother's perception of “insufficient breast milk” was also the main reason for introducing other foods. Optimal breastfeeding promotion campaigns need to be carried out within the existing health care system such as the antenatal, after delivery and vaccination clinics. Journal of Nepalgunj Medical College Vol.13(1) 2015: 32-39